Effects of match location, match result and the quality of opposition in training load on a two-matches week in a top-class elite European soccer team - Oliveira, Rafael (2022)
: It is well known that soccer and performance can be affected by situational variables. Thus, the purpose of this study is to analyse effects of match location, match result and level of opponents in training load on the two following days of the match (match-day [MD] plus [+], MD+1; MD+2) in a top-class elite soccer European team that played in UEFA Champions League during in-season 2015/16. Nine players participated in this study. A global positioning system (GPS) was used to measure total distance covered, distances of different exercise training zones (1–5) and average speed (AvS). The session rating of perceived exertion (s-RPE) and Hooper Index scores (fatigue, stress, sleep quality, delayed onset muscle soreness-DOMS) were also collected. Data was analysed regarding the two following days of a match. All weeks analysed included two matches. The main results showed higher values of DOMS, ES= 1.69, and fatigue ES=1.25, on the day following an away-win match. It was also observed higher values of sleep quality ES=1.44, zone 1, ES=-4.35, and AvS, ES=-12.65, but lower values of s RPE, ES=3.52, on the day following away-win match against a national top-level opponent (TLO). Finally, higher values for zone 3, ES=1.71, and lower value for AvS, ES=-6.06 were observed on the day following away-win match. Total distance, AvS and zone 4 were higher after playing national opponents in MD+1 than MD+2 and/or champions league opponents. The pattern of training load seems to be affected by situational variables. In general, the higher the quality of the opponents, the higher Hooper index in MD+1. S-RPE seems to be higher after playing a bottom level opponent when compared with the other opponents. Also, after playing national opponents, total distance, zone 1 and zone 4 were higher than against international opponents.